A Suggested Arrangement of Grooves for Enhancing the Return Loss Performance Characteristics of Submillimeter-Wave Corrugated Horns - Matsunaga, Mayumi; Matsunaga, Toshiaki (Publications of the Astronomical Society of Japan, 2007)
A new arrangement of grooves by which the return loss performance characteristics of submillimeter-wave corrugated horns have been greatly improved is presented. Corrugated horns equipped with grooves arranged as per the way introduced in this paper each have been found to be capable of radiating a field with return losses of $-$ 28 or less dB, while maintaining maximum cross-polarization levels of $-$ 45 or less dB within a frequency range of 385 GHz to 500 GHz. This is a performance level greater than the goal set for feed horns for radio telescopes. The reason for this enhancement of the return losses is because the part often referred to as the “mode-transforming section” has been formed differently, that is to say the grooves are arranged differently in this part than in the conventional mode-transforming section. Specifically, the number of grooves provided in this new mode-transforming section has been decreased vis-à-vis that of those in the conventional mode-transforming section, and these grooves are arranged with their depths varied in accordance with the angles of the section’s flares. Further, the structure of each groove has been so simplified that it is a parallelogram in cross section, and the part outside the mode-transforming section is provided with grooves that are in uniform depth and width being arranged at a regular interval. Despite the simplicity of the grooves, the return losses of submillimeter-wave corrugated horns have been greatly enhanced while their cross-polar radiation fields are maintained at low levels.